The starting date for maternity leave for mothers of premature babies with late and article 207, paragraph 2, of Law Law No. 8.112/1990 (Revista do Tribunal Regional Federal da 3ª Região, 2016)
The constitutional right of maternity leave is intended not only to protect the biological mother, but especially for the socio-affective development of the baby, the process of learning the roles of father, mother and brother, and building up the affective bonds in the family. So considering, the initial term for maternity leave for mothers of premature babies who require long hospital stay, cannot be the day of the birth, as does the Law 8.112/90, but rather the day it is granted hospital discharge. Until that day, the mother is entitled to use a sick leave for family care instead of maternity leave.
Keywords: initial term; maternity leave; premature babies; federal employess; unconstitutionality